An intersectional approach to evaluating consumer financial literacy. Issue 4 (December 2016) - Nejad, Mohammad; O'Connor, Genevieve
Abstract This study applies a novel approach to explore consumer financial literacy—the necessary skills and knowledge to make personal financial decisions—across different demographic groups. Rather than exploring demographic variables independently of each other, an intersectional approach is employed to identify the most critical and vulnerable consumer groups in light of financial literacy. A survey of 1047 respondents from a panel of consumers residing in the United States demonstrates that identifying the most critical and vulnerable consumer groups is achieved using an intersectional approach. For example, although we find Generation Y exhibits lower financial literacy compared with previous generations, by examining the demographic variables simultaneously, we find that Generation Y females who are members of ethnical minorities are at the greatest risk of being financially vulnerable. Implications for research and financial literacy programs are discussed.